The Influence of the E-Samsat Program and Taxpayer Satisfaction on Taxpayer Compliance in Nagan Raya Samsat Office - Erlina, Erlina; Marlina, Lilis (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Non-compliance in tax payments, particularly motor vehicle taxes, poses a significant threat to the state, impacting its financial stability and national development. This descriptive quantitative research, framed within a theoretical context, explores the consequences of tax non-compliance on government programs and the country’s standing in the global arena. The study focuses on motorized vehicle taxpayers registered at the Nagan Raya SAMSAT Joint Office, with a sample size of 100 selected using the Slovin algorithm. The data collection strategy employed in this study was a questionnaire. The resulting data is processed using SPSS. The results showed that the E-Samsat initiative had a marginally meaningful effect on required compliance. Taxpayer satisfaction partially has a big effect on taxpayer compliance. The findings of testing the two factors X have a simultaneous influence on taxpayer compliance. The theoretical framework highlights the vital role of effective tax compliance in supporting government initiatives and maintaining international credibility. The study’s contribution lies in providing insights that can guide policymakers and tax authorities in enhancing compliance, ensuring a more robust financial foundation for the state, and bolstering national development.